(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Veronika P. Gredel (St. Petersburg, Russian Federation) E. Zamyatin’s “We” is interpreted as peculiar of author’s himself and imaginary co-author’s D-503. For author “We” is cosmos, for D-503 – numbers of One State. “We” represents a synthesis of genres formations, which can be identified as composition-sense steps of the novel: from author’s point of view – an anti-utopia novel and a classical tragedy; from narrator’s D-503 side – a synopsis, diary and drama. Key words: E. Zamyatin, genre, “WE”, modus, concept, epitaph, “the wisest of all lines”. DOI 10.23683/1995-0640-2018-4-179-187